Pengaruh Leverage, Likuiditas, Total Asset Turnover dan Asset Growth terhadap Risiko Sistematis pada Perusahaan yang Terdaftar di Jakarta Islamic Index - Vina Fatimatuz Zahroh; Agustina Widodo (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research aims to prove the influence of leverage, liquidity, total asset turnover and asset growth on systematic risk in companies listed on the Jakarta Islamic Index. The population used in this research is companies listed on the Jakarta Islamic Index on the Indonesia Stock Exchange in 2018-2022. The sample selection technique uses purposive sampling. The data analysis technique uses multiple linear regression analysis. The results of this study show that leverage has an insignificant negative effect on systematic risk, liquidity has an insignificant positive effect on systematic risk, total asset turnover has an insignificant positive effect on systematic risk and asset growth has an insignificant positive effect on systematic risk in companies registered with Jakarta Islamic Index. The Adjusted R2 value is 0.088, so it can be interpreted that 8.8% of the systematic risk variables of companies listed on the Jakarta Islamic Index can be explained by the four independent variables, namely leverage, liquidity, total asset turnover and asset growth. Meanwhile, the remaining 91.2% is explained by other variables not examined in this study.